Asymmetric Supercapacitors Using Chemically Prepared MnO2 as Positive Electrode Materials. Issue 9 (2nd August 2017) - Attias, Ran; Sharon, Daniel; Borenstein, Arie; Malka, David; Hana, Ortal; Luski, Shalom; Aurbach, Doron
Abstract : Chemically prepared manganese dioxide (CMD), which is traditionally used as a cathode material for Li-ion batteries, was tested and characterized for the first time as a positive electrode material for hybrid supercapacitors with two different aqueous electrolyte solutions (6 M KOH and 0.5 M K2 SO4 ). The CMD electrodes exhibit distinct electrochemical characteristics that depend on the electrolyte solution used. The CMD electrodes show higher specific capacitance in the basic electrolyte solution, 137 F/g, at a current density of 0.1 A/g. Asymmetric supercapacitors comprising CMD positive electrodes and activated carbon negative electrodes were fabricated and tested within an electrochemical window wider than the thermodynamic voltage limitation for aqueous solutions. The asymmetric supercapacitors based on KOH and K2 SO4 showed very good electrochemical stability during more than 7000 charge–discharge cycles and reasonable energy and power density. The electrochemical performance of CMD/AC asymmetric supercapacitors, their easy assembly, and their low cost make these super capacitors promising as practical energy-storage devices.